Death in the jungle : murder, betrayal, and the lost dream of Jonestown - Fleming, Candace (Anne Schwartz Books, 2025)
A chronicle of one of American history's most notorious cults, a book including first-person accounts follows Jim Jones from humble origins to "Jonestown" in Guyana, South America, and traces his transformation of Peoples Temple into a nefarious experiment in mind control.